Developing reading and writing skills - Estacio, Ma. Joahna M. (Quezon City : Phoenix Publishing House, Inc., 2016)
After completing this course, the learners are expected to have gained knowledge and skills related to critical reading and academic writing. Three units with related and well-organized lessons aim to discuss and to give ample practice to learners so they may prepare themselves to tackle challenging reading and writing tasks that they will encounter when they practice their chosen profession in the near future. For teachers, this book provides flexibility in carrying out the lessons and developing their creativity in engaging the learners to be active and realize their role not just as a source of knowledge, but as a facilitator of learning.
Unit 1. The reading process -- Unit 2. Reading into writing -- Unit 3. Writing in the disciplines and for professions.